Microbiota-derived butyrate dynamically regulates intestinal homeostasis through regulation of actin-associated protein synaptopodin - Wang, Ruth X. (Proc Natl Acad Sci U S A, 2020)
The intestinal mucosa exists in dynamic balance with trillions of luminal microbes. Disruption of the intestinal epithelial barrier, commonly observed in mucosal inflammation and diseases such as inflammatory bowel diseases (IBDs), is often associated with dysbiosis, particularly decreases in species producing short-chain fatty acids (SCFAs), such as butyrate. It remains unclear to what extent microbiota-derived factors contribute to the overall maintenance of intestinal homeostasis. Initial studies revealed that butyrate selectively promotes epithelial barrier function and wound healing. We aimed to define the specific mechanism(s) through which butyrate contributes to these epithelial responses. Guided by an unbiased profiling approach, we identified the dominant regulation of the actin-binding protein synaptopodin (SYNPO). Extensions of this work revealed a role for SYNPO in intestinal epithelial barrier function and wound healing. SYNPO was localized to the intestinal epithelial tight junction and within F-actin stress fibers where it is critical for barrier integrity and cell motility. Butyrate, but not other SCFAs, induced SYNPO in epithelial cell lines and murine colonic enteroids through mechanisms possibly involving histone deacetylase inhibition. Moreover, depletion of the microbiota abrogated expression of SYNPO in the mouse colon, which was rescued with butyrate repletion. Studies in Synpo-deficient mice demonstrated exacerbated disease susceptibility and increased intestinal permeability in a dextran sulfate sodium colitis model. These findings establish a critical role for the microbiota and their products, specifically butyrate, in the regulated expression of SYNPO for intestinal homeostasis and reveal a direct mechanistic link between microbiota-derived butyrate and barrier restoration.